Contribution of martial arts participation to interpersonal intelligence in adolescents: An ex post facto study - Alif, Muhammad Nur; Komarudin; Septiadi, Firman; Mulyana (UIR Press, 2025)
Background: Adolescence is a crucial stage for identity formation and social skill development, yet many adolescents struggle with emotional regulation and building healthy interpersonal relationships. Martial arts activities are known to instill discipline, respect, and cooperation, contributing to socio-emotional growth. However, empirical studies examining the direct relationship between martial arts participation and interpersonal intelligence especially in the Indonesian adolescent context remain limited. Objectives: This study aims to analyze the role of martial arts activities in supporting the development of adolescent interpersonal intelligence through the values of discipline, cooperation, and respect for others. Methods: This study used an ex post facto method with a quantitative approach. The subjects were 87 adolescents who actively participated in martial arts training in pencak silat, karate, and taekwondo in Bandung City. The instruments used included a martial arts activity questionnaire and a validated interpersonal intelligence scale. Findings/Results: The results of the compare mean analysis showed that the highest average score in interpersonal intelligence was found in the empathy indicator (M = 17.2; SD = 2.1), while in martial arts activities the highest was found in the activity type indicator (M = 13.4; SD = 2.2). In addition, the results of simple linear regression showed a 36.4% contribution of martial arts activities to interpersonal intelligence (R2 = 0.364; F = 122.77; p = 0.001). Conclusion: The findings indicate that martial arts participation contributes positively to adolescents’ socio-emotional development, particularly by strengthening interpersonal intelligence. This study provides an important contribution by offering empirical evidence for the role of sports-based character education in shaping interpersonal skills. However, the limited sample and the use of an ex post facto design reduce the generalizability and do not allow causal interpretation. Future research should involve larger and more diverse participants as well as stronger methodological designs to better understand how martial arts influence adolescents’ interpersonal development.